Regulatory Factors for tRNA Modifications in Extreme- Thermophilic Bacterium Thermus thermophilus - Hori, Hiroyuki (Frontiers in Genetics, 2019)
Thermus thermophilus is an extreme-thermophilic bacterium that can grow at a wide range of temperatures (50-83ºC). To enable T. thermophilus to grow at high temperatures, several biomolecules including tRNA and tRNA modification enzymes show extreme heat-resistance. Therefore, the modified nucleosides in tRNA from T. thermophilus have been studied mainly from the view point of tRNA stabilization at high temperatures. Such studies have shown that several modifications stabilize the structure of tRNA and are essential for survival of the organism at high temperatures. Together with tRNA modification enzymes, the modified nucleosides form a network that regulates the extent of different tRNA modifications at various temperatures. In this review, I describe this network, as well as the tRNA recognition mechanism of individual tRNA modification enzymes. Furthermore, I summarize the roles of other tRNA stabilization factors such as polyamines and metal ions.